Книга джунглей - Киплинг Редьярд (Махаон, 2013)
Дополнительный тираж Экземпляры: Ф. 4 (20200708) / Инвентарный номер: 44044 / Цена: 150.00 / Сис.шифр: 84(4 Вел) / Авт.знак: К 42 / ГРНТИ: 17.82.93 / ББК: 84(4 Вел)